The AASPIRE practice-based guidelines for the inclusion of autistic adults in research as co-researchers and study participants. (November 2019) - Nicolaidis, Christina; Raymaker, Dora; Kapp, Steven K; Baggs, Amelia; Ashkenazy, E; McDonald, Katherine; Weiner, Michael; Maslak, Joelle; Hunter, Morrigan; Joyce, Andrea
As interest in autism in adulthood grows, so does the need for methods to promote the inclusion of autistic adults in research. Our objective was to create practice-based guidelines for the inclusion of autistic adults, both as research team members and as study participants. We conducted an institutional ethnography of three closely related research partnerships that used participatory methods with autistic adults over the years 2006–2018. We used an iterative approach which combined discussions with community and academic partners and artifact review. Guidelines to promote the inclusion of autistic adults as co-researchers focus on being transparent about partnership goals, clearly defining roles and choosing partners, creating processes for effective communication and power-sharing, building and maintaining trust, disseminating findings, encouraging community capacitation, and fairly compensating partners. Guidelines to promote the inclusion of autistic adults as study participants focus on maximizing autonomy and inclusion, creating an accessible consent process, offering multiple modes of participation, adapting survey instruments for use with autistic adults, creating accessible qualitative interview guides, and handling data from proxy reporters. Although these practice-based guidelines may not apply to all research teams, we hope that other researchers can capitalize on these practical lessons when including autistic adults in research.